Studi Penerapan Sky Garden pada Rumah Susun Jatinegara Barat - Hakim, Hakim (Program Studi Magister Manajemen Lingkungan, 2023)
Through economic progress has transformed the traditional urban space into a modern high-rise object city. This requires spatial solutions and alternative technologies to repopulate the environment that was once very intrinsic for citizens to interact with. This research considers sky court and sky garden in terms of the social, economic, environmental, and spatial benefits they provide to urban habitats. This research has the potential to become an 'alternative' social space that can become part of a wider multi-level open space infrastructure to fill the loss of open space in urban habitats. This study aims to determine the level of understanding of residents on the importance of plants to improve the quality of the environment in which they live. Quantitative descriptive method to be able to describe a picture of a situation or event that is taking place naturally. The results of this study indicate that sky garden is an alternative for greening residential areas. Skygarden with the typical type with one edge position, was chosen as the residents' first choice because they feel more familiar with the care.